Invesmento diferencial em compostos químicos nos tecidos de galhas induzidas por Palaeomystella olygophaga (Lepidoptera) em Macairea radula (melastomataceae) - Naves, Guilherme de Faria Silva (2020)
Galling insects manipulate the host plant tissues into own benefit. Because of galling feeding activity both structural and metabolical occurs leading to chances in the associated fauna. Herein, galls induced by the Palaeomystella oligophaga (Lepidoptera) on Macairea radula (Melastomataceae) dependes on the constant larval feeding stimulus for the gall establishment and development. These galls, besides being large, have a coloration ranging from light green to dark red and have thick parenchyma, with projections and trichomes that give them an even more conspicuous appearance. The gall showed two tissue compartments, the storage and nutritive tissue and here, we look for investigate the levels of oxidative stress and if there is a chemical differential investment on these compartments. In addition, we look for investigate the relationship between the gall coloration and the concentration of carbohydrates. So, we aimed to quantify (I) nutritive compounds such as sugars, polysaccharides, starch, proteins and lipids, (II) defensive and signaling compounds as phenolics, (III) oxidative stress and (IV) associate possible investments in these compounds with the gall coloration. Polysaccharides, MDA (oxidative stress meter), and phenolic compounds were found in high concentration in the outermost portion of the gall cortex (storage tissue). However, the total soluble sugar occurred in high concentration in the nutritive tissue. The red galls may be associated with high concentration of water-soluble polysaccharides.